ปรากฏการณ์ฆ่าตัวตาย ในนักเรียน นักศึกษาไทย มุมมองด้านสังคมศาสตร์และการศึกษา - จามจุรี ดนุลดา (Journal of Research and Curriculum Development, 2011)
บทคัดย่อไม่สมบูรณ์ Suicide in Thai Student: Sociology and Education Perspective Suicide or self-destruction is a problem that should be able to prevented, especially in a student, who is a future of nation. This article focuses on two issues: (1) what are the factors that influence suicide in student; is educational system one of the major factors causing the suicide? (2) why cannot the education prevent students from committing suicide, and help them solve problems? The concept of Emile Durkheim’s theory of suicide, together with issues related to the Thai education was used. The issues of student’s suicide were analyzed in three aspects, which are firstly, the aspect of relationship between individual and society; secondly, rules, regulation and social norms in Thai society, and thirdly, the aspect of educational system toward individual and the aspect of social values towards the educational system.